FACTORS AFFECTING THE FUNCTIONAL INDEPENDENCE OF PATIENTS AMPUTEES TRANSFEMORAL PROSTHESES (Fiep Bulletin - online, 2014)
Introduction: Amputation means a partial or total withdrawal of a member or more, may be surgical or traumatic. Already a transfemoral amputation refers to amputations performed between the knee disarticulation and hip, divided into proximal, middle and distal. Can occur for various reasons trauma, vascular processes, thrombosis, tumors, infections, inborn processes and rheumatoid arthritis. The primary objective of this study was to identify factors that affect the level of functional independence of patients transfemoral prostheses Rehabilitation Center Gurgacz Assisi. Methodology: This is a field study of epidemiologic and evaluative, quantitative cross-sectional survey with a sample comprised 12 individuals: 4 females and 8 males, aged 19-78 years. Data were collected through a questionnaire prepared by the author to evaluate the stump and the questionnaire "Measure Functional Amputee" translated and validated in Brazil by Kageyama in 2007, the interviews occurred FAG Rehabilitation Center in the months of June and July 2013. Results: After the questionnaires showed that the responses were less satisfactory individuals with higher ages being 56, 76 and 78 years, with shorter use of this prosthesis with 8, 9 and 10 months, changes in sensitivity and grip the healing of the stump. Conclusion: From these data, we found that older age and short time of use of the prosthesis, as well as adherence healing and increased sensitivity leads to a stump in the level of functional independence down to the prosthesis, allowing physiotherapy direct their actions regarding rehabilitation, and also showing the need for further research on the topic discussed.
Keywords: transfemoral amputation; functional measure for amputees; stump complications.